Review of amphipods of the Melita group (Amphipoda: Melitidae) from the coastal waters of Sakhalin Island (Far East of Russia). II. Genera Quasimelita Jarrett & Bousfield, 1996 and Melitoides Gurjanova, 1934 - Labay, Vjacheslav S. (Zootaxa, 2014)
Based on new material, three new species of the genus Quasimelita are described: Q. tolyza sp. nov., Q. jarettii sp. nov. and Q. serraticoxae sp. nov. from northern shelf of Sakhalin Island and contiguous area. The new species of the genus Melitoides, M. kawaii sp. nov. is described from north-east shelf of Sakhalin Island. Keys to the world species of genera Quasimelita and Melitoides are provided. Cladistic analysis of morphological relationships within genera Quasimelita and Melitoides are implemented.